PENGARUH PERIKLANAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE MEREK SAMSUNG - Winda Pramita; Iwan Kurniawan Subagja (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
This study aims to analyze the influence of advertising and brand image on Samsung brand purchasing decisions. The population in this study were 137 students of the Faculty of Economics, University of Krisnadwipayana who used Samsung smartphones consisting of 84 students majoring in management and 53 students majoring in accounting. The sampling technique in this study used a non-probability sampling technique, which used purposive sampling technique, which was an economics faculty student who used a Samsung mobile phone and who had seen a Samsung advertisement. The results showed that there was an influence of advertising and brand image on the purchase decision of the Samsung brand at the Faculty of Economics at University of Krisnadwipayana.